Tumor-targeted Chlorotoxin-coupled Nanoparticles for Nucleic Acid Delivery to Glioblastoma Cells: A Promising System for Glioblastoma Treatment - Costa, Pedro M. (2013)
The present work aimed at the development and application of a lipid-based nanocarrier for targeted delivery of nucleic acids to glioblastoma (GBM). For this purpose, chlorotoxin (CTX), a peptide reported to bind selectively to glioma cells while showing no affinity for non-neoplastic cells, was covalently coupled to liposomes encapsulating antisense oligonucleotides (asOs) or small interfering RNAs (siRNAs). The resulting targeted nanoparticles, designated CTX-coupled stable nucleic acid lipid particles (SNALPs), exhibited excellent features for in vivo application, namely small size (<180 nm) and neutral surface charge. Cellular association and internalization studies revealed that attachment of CTX onto the liposomal surface enhanced particle internalization into glioma cells, whereas no significant internalization was observed in noncancer cells. Moreover, nanoparticle-mediated miR-21 silencing in U87 human GBM and GL261 mouse glioma cells resulted in increased levels of the tumor suppressors PTEN and PDCD4, caspase 3/7 activation and decreased tumor cell proliferation. Preliminary in vivo studies revealed that CTX enhances particle internalization into established intracranial tumors. Overall, our results indicate that the developed targeted nanoparticles represent a valuable tool for targeted nucleic acid delivery to cancer cells. Combined with a drug-based therapy, nanoparticle-mediated miR-21 silencing constitutes a promising multimodal therapeutic approach towards GBM.